Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the value of [tex]\( y \)[/tex] when [tex]\( x \)[/tex] equals 11 in the equation [tex]\( 8x + 6y = 28 \)[/tex], follow these steps:
1. Substitute [tex]\( x = 11 \)[/tex] into the equation:
[tex]\[ 8(11) + 6y = 28 \][/tex]
2. Calculate [tex]\( 8 \times 11 \)[/tex]:
[tex]\[ 88 + 6y = 28 \][/tex]
3. Subtract 88 from both sides of the equation to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ 6y = 28 - 88 \][/tex]
4. Simplify the right-hand side:
[tex]\[ 6y = -60 \][/tex]
5. Solve for [tex]\( y \)[/tex] by dividing both sides by 6:
[tex]\[ y = \frac{-60}{6} \][/tex]
6. Perform the division:
[tex]\[ y = -10 \][/tex]
So, the value of [tex]\( y \)[/tex] when [tex]\( x = 11 \)[/tex] is [tex]\( -10 \)[/tex].
1. Substitute [tex]\( x = 11 \)[/tex] into the equation:
[tex]\[ 8(11) + 6y = 28 \][/tex]
2. Calculate [tex]\( 8 \times 11 \)[/tex]:
[tex]\[ 88 + 6y = 28 \][/tex]
3. Subtract 88 from both sides of the equation to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ 6y = 28 - 88 \][/tex]
4. Simplify the right-hand side:
[tex]\[ 6y = -60 \][/tex]
5. Solve for [tex]\( y \)[/tex] by dividing both sides by 6:
[tex]\[ y = \frac{-60}{6} \][/tex]
6. Perform the division:
[tex]\[ y = -10 \][/tex]
So, the value of [tex]\( y \)[/tex] when [tex]\( x = 11 \)[/tex] is [tex]\( -10 \)[/tex].
Answer:
Step-by-step explanation:
To find the value of
y when
=
11
x=11 in the equation
8
+
6
=
28
8x+6y=28, follow these steps:
Substitute
=
11
x=11 into the equation:
8
(
11
)
+
6
=
28
8(11)+6y=28
Simplify the left-hand side:
88
+
6
=
28
88+6y=28
Subtract 88 from both sides to isolate the term with
y:
6
=
28
−
88
6y=28−88
Simplify the right-hand side:
6
=
−
60
6y=−60
Divide both sides by 6 to solve for
y:
=
−
60
6
y=
6
−60
Simplify the fraction:
=
−
10
y=−10
Therefore, when
=
11
x=11, the value of
y is
−
10
−10.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.